GSK3 and its interactions with the PI3K/AKT/mTOR signalling network. (August 2017) - Hermida, Miguel A.; Dinesh Kumar, J.; Leslie, Nick R.
Abstract: Glycogen Synthase Kinase-3 (GSK3 or GSK-3) is a promiscuous protein kinase and its phosphorylation of its diverse substrates has major influences on many areas of physiology and pathology, including cellular metabolism, lineage commitment and neuroscience. GSK3 was one of the first identified substrates of the heavily studied oncogenic kinase AKT, phosphorylation by which inhibits GSK3 activity via the formation of an autoinhibitory pseudosubstrate sequence. This has led to investigation of the role of GSK3 inhibition as a key component of the cellular responses to growth factors and insulin, which stimulate the class I PI 3-Kinases and in turn AKT activity and GSK3 phosphorylation. GSK3 has been shown to phosphorylate several upstream and downstream components of the PI3K/AKT/mTOR signalling network, including AKT itself, RICTOR, TSC1 and 2, PTEN and IRS1 and 2, with the potential to apply feedback control within the network. However, it has been clear for some time that functionally distinct, insulated pools of GSK3 exist which are regulated independently, so that for some GSK3 substrates such as β-catenin, phosphorylation by GSK3 is not controlled by input from PI3K and AKT. Instead, as almost all GSK3 substrates require a priming phosphorylated residue to be 4 amino acids C-terminal to the Ser/Thr phosphorylated by GSK3, the predominant form of regulation of the activity of GSK3 often appears to be through control over these priming events, specific to individual substrates. Therefore, a major role of GSK3 can be viewed as an amplifier of the electrostatic effects on protein function which are caused by these priming phosphorylation events. Here we discuss these different aspects to GSK3 regulation and function, and the functions of GSK3 as it integrates with signalling through the PI3K-AKT-mTOR signalling axis.